Tinjauan Pustaka: Sindrom Vena Kava Superior - Chyntia Triana Putri; Adrianison Adrianison; Sri Melati Munir (Fakultas Kedokteran Universitas Riau, 2024)
Superior Vena Cava Syndrome (SVCS) includes various clinical signs and symptoms due to external compression and intrinsic obstruction of superior vena cava (SVC) itself or the superior cavo-atrial junction that cause reducing of blood flow. Infection becomes main etiology in previous decades but development in antibiotics treatment and improvement of socio-economyc condition made incidence of SVCS due to infection decreased. SVCS due to malignancy recently reach 60-90% of overall cases. 78-85% of SVC obstructions due to malignancy are caused by lung cancer and 80% of it is right lesion. Historically SVCS is considered as an oncology emergency condition and become one of a few indications for palliative radiotherapy. This literature review will explain the pathophysiology, etiology, diagnosis and management of SVCS with the aim of providing timely and effective intervention to treat the causes of this syndrome so that it can significantly relieve symptoms and improve the quality of life of patients with SVCS.